Frailty predicts trajectories of quality of life over time among British community-dwelling older people - Kojima, Gotaro; Iliffe, Steve; Morris, Richard.W.; Taniguchi, Yu; Kendrick, Denise; Skelton, Dawn A.; Masud, Tahir; Bowling, Ann (Springer International Publishing, 2016)
Purpose: To investigate associations between baseline frailty status and subsequent changes in QOL over time among community-dwelling older people.